Effects of IPA treatment on the photovoltaic performance of bulk heterojunction organic solar cells. (July 2019) - Aghassi, Ali; Fay, Cormac D.
Abstract: The treatment of the bulk heterojunction (BHJ) active layer by polar solvents such as alcohols is regarded as a simple, yet effective technique to enhance the power conversion efficiency (PCE) of organic solar cells (OSCs). This study investigated the impact of isopropyl alcohol (IPA) on the photovoltaic performance of two BHJ solar cell devices composed of (a) Poly[N-9′-heptadecanyl-2, 7-carbazole-alt-5, 5-(4′, 7′-di-2-thienyl-2′, 1′, 3′-benzothiadiazole)] (PCDTBT) and (b) 7, 7′-[4, 4-Bis(2-ethylhexyl)-4H-silolo[3, 2-b:4, 5-b′] dithiophene-2, 6-diyl]bis [6-fluoro-4-(5′-hexyl-[2, 2′-bithiophen]-5-yl)benzo[c][1, 2, 5]thiadiazole (p-DTS(FBTTh2 )2 as donors and [6, 6]-phenyl-C61-butyric acid methyl ester (PC60 BM) as the acceptor in both instances. The physical characteristics of the active layers before and after the treatment were established by UV–Vis absorption and water contact angle measurements. The photovoltaic characteristics of the devices were measured using current density-voltage and external quantum efficiency (EQE) measurements. In addition, a light-intensity dependency technique was employed to study the recombination dynamics of charge carriers under steady-state conditions. The finding reveals that the characteristics of the films remain almost unchanged and that none of the key factors contributing to the PCE of the solar cells were significantly influenced by the IPA treatment. It is thus concluded that the treatment with IPA may not be an effective method to enhance the photovoltaic performance of solar cell devices, as opposed to reports within the literature. Highlights: Bulk heterojunction organic solar cells were subjected to post-production IPA treatment. BHJ films characteristics as well as Photovoltaic performance of solar cell devices were examined. Charge carriers mobility and recombination were studied as a function of the IPA treatment. No significant enhancement was observed following the treatment in contrast to some reports in the literature.